Pendidikan Sejarah di Malaysia Dewasa ini: Sejauh Manakah ia Relevan kepada Pembinaan Nasion? - Adam, Ahmat (SUSURGALUR, 2014)
IKHTISAR: Pendidikan sejarah, bagi negara multi-etnik dan multi-bahasa seperti di Malaysia, memerlukan perhatian khusus dari pemerintah karena ia bisa dijadikan sebagai sarana untuk menanamkan semangat âesprit de corpâ atau rasa persatuan antara sesama warga negara. Sementara itu, pendidikan sejarah di Malaysia menempuh era baru apabila mata pelajaran sejarah dijadikan subjek wajib lulus oleh Kementerian Pendidikan Malaysia untuk ujian SPM (Sijil Pelajaran Malaysia) menjelang akhir tahun 2013. Tetapi untuk pelaksanaan yang bijak, rencana pengajaran sejarah di sekolah-sekolah harus membereskan beberapa masalah, seperti perancangan kurikulum yang semrawut, isi silabus dan materi buku pelajaran yang tidak seimbang, serta pendekatan yang membawa persepsi bahwa sejarah Malaysia tidak inklusif untuk semua suku. Ikut dibicarakan adalah langkah-langkah yang harus diambil agar pengajaran sejarah di sekolah berdasarkan prinsip dan metode sejarah yang nenekankan objektivitas dan pencarian kebenaran. Makalah berikut ini membicarakan isu-isu pengajaran sejarah di sekolah-sekolah dan coba membahas persoalan-persoalan pendidikan sejarah serta memberikan saran-saran untuk mencari jalan keluar dengan tujuan menyelesaikan masalah-masalah tersebut demi peningkatan kualitas pengajaran dan penelitian sejarah.KATA KUNCI: Pendidikan sejarah, negara-bangsa Malaysia, guru, siswa, dan kurikulum, serta objektivitas dalam sejarah. ABSTRACT: This article entitled âHistory Education in Malaysia Today: Which Far it Relevant to Development of the Nation?â. History education, for a multi-ethnic and multi-language country such as in Malaysia, require special attention from the government because it can be used as a means to instill the spirit of "esprit de corp" or a sense of unity among the citizens. Beside, education in Malaysia has now reached a new turn when passing the history subject is made compulsory for all secondary school students sitting for the School Certificate Examinations. This requirement which was first implemented for candidates who sat for the said examinations towards the end of 2013, however, means that a review of the history curriculum and syllabus is needed in order to ensure that the bureaucrats involved in the drafting of a new curriculum and syllabus understand the proper notion of the historical method and the correct understanding of historical concepts such as objectivity and the search for truth. Also needed is the conscious effort at ensuring the writing of school textbooks are free from bias and ideological propaganda in order to demonstrate inclusiveness for all Malaysians. The following article attempts to demonstrate the weaknesses inherent in the present state of affairs in regard to history teaching in secondary schools and to propose certain steps in order to promote a better understanding of the concept of historical inquiry and enhance the quality of history teaching in schools. Â KEY WORD: History education, nation-state of Malaysia, teachers, students, and curriculum, and objectivity in history.About the Author: Profesor Emeritus Dr. Ahmat Adam ialah seorang ilmuwan dan sejarawan independen dari Malaysia, yang pakar tentang sejarah pers di Indonesia. Banyak melakukan penelitian dan menulis buku, diantaranya adalah Sejarah Awal Pers dan Kebangkitan Kesadaran Keindonesiaan (Jakarta: Penerbit Hasta Mitra, 2003). Untuk kepentingan akademik, penulis bisa dihubungi dengan alamat emel: ahmatadam41@gmail.comHow to cite this article? Adam, Ahmat. (2014). âPendidikan Sejarah di Malaysia Dewasa ini: Sejauh Manakah ia Relevan kepada Pembinaan Nasion?â in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.2(1), Maret, pp.101-114. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808, ISSN 2302-5808. Chronicle of the article: Accepted (December 22, 2013); Revised (February 2, 2014); and Published (Maret 24, 2014).